High-entropy materials as electrocatalysts for energy-related applications - Sivanantham, Arumugam; Santhanagopalan Shridharan, Tatachari; Tan, Runfa; Cho, In Sun (High-Entropy Alloys: Design, Manufacturing, and Emerging Applications, 2024)
High-entropy materials (HEMs) have emerged as highly adaptable electrocatalysts in advanced energy-related applications. This chapter investigates the intricacies of HEMs, exploring their composition–structure–activity relationships and delineating a comprehensive road map detailing recent breakthroughs in electrochemical energy-related applications. The discussion meticulously dissects various structural aspects of HEMs, underscoring the pivotal roles played by metal element composition, overall structure, and the synergistic effects of multiple sites. Based on recent progress, emphasis is placed on elucidating the challenges encountered and the unique characteristics inherent in HEMs across diverse applications. This chapter serves as an invaluable resource, offering abundant insights into the multifaceted role of HEMs as electrocatalysts in advanced energy-related applications. Furthermore, it provides valuable guidance for the future design and exploration of potential HEM candidates, shaping the trajectory of energy-related innovations.
Keywords: catalysis; catalytic mechanism; composition–structure–activity relationship; continuum adsorption energy; electrocatalyst; Electrochemical energy conversion; electrochemistry; energy storage; high-entropy materials; materials science; organic compound; road-map in energy applications; superior performance; synergistic effect; tunable property